Co-solvent Selection for Supercritical Fluid Extraction of Essential Oil and Bioactive Compounds from Polygonum minus - Markom, Masturah; Hassim, Norsyamimi; Anuar, Nurina; Baharum, Syarul Nataqain (ASEAN Journal of Chemical Engineering, 2012)
This study evaluated the biological activity (antioxidant assay) of Polygonum minus extracted using Supercritical Fluid Extraction (SFE) added with different types of co-solvents. The seven co-solvents employed were water, methanol, ethanol, 50% methanol, 50% ethanol, 70% methanol and 70% ethanol for selection of the best co-solvent prior to optimization of SFE. 70% methanol produced the highest total yield of extract (33.1%) compared to other co-solvents. The antioxidant capacity was then evaluated using four different assays: the total phenolic content (TP), the total flavonoid content (TF), the ferric reducing/antioxidant power (FRAP) and the free radical-scavenging capacity of 2,2-diphenyl-1-picrylhydrazyl (DPPH). The highest TP and TF were from 70% methanol extract (11.2 ± 0.15 mg GAE/g sample (mg GAE/g) and 11.9 ± 0.03 mg CAE/g sample (mg CEQ/g) respectively). 70% metanol extract also showed the highest FRAP value (346.7 ± 0.66 µmol Fe (II)/g sample) and the highest percentage of DPPH radical inhibition was also shown by 70% methanol extract (88.7 ± 0.40%). There was a positive correlation between the antioxidant capacity (FRAP and DPPH) with those of TP and TF contents. Therefore, the best co-solvent chosen for further optimization of SFE is 70% methanol.